2018 Vegetable Production Handbook Chapter 4: Integrated Pest Management - Peter J. Dittmar; Nicholas S. Dufault; Joseph W. Noling; Philip Stansly; Nathan Boyd; Mathews L. Paret; Susan E. Webb (EDIS, 2018)
This 11-page fact sheet is the fourth chapter in the 2018 Vegetable Production Handbook. Peter J. Dittmar, Nicholas S. Dufault, Joseph W. Noling, Philip Stansly, Nathan Boyd, Matthews L. Paret, and Susan E. Webb, and published by the Horticultural Sciences Department, 2018.